Access to Veterinary Drugs in Sub-Saharan Africa: Roadblocks and Current Solutions - Jaime, Glória; Hobeika, Alexandre; Figuié, Muriel (Frontiers in Veterinary Science, 2022)
Background Access to veterinary drugs for livestock has become a major issue over the last decade. Analysis has tended to focus on the demand for these products, while studies looking at the drivers behind their use generally focus on farmer behavior and interactions between veterinarians and farmers. However, the use of drugs also depends on structural factors that determine the functioning of the drug supply chain and farmers' access to the drugs. This article presents an overview of the factors that limit access to veterinary drugs in sub-Saharan Africa (SSA) as well as the international policy tools and arrangements that claim to improve it. Methods We have conducted a scoping review of the scientific and grey literature as well as the publicly-available data from both the animal health industry and international organizations. We aimed to gather information on the veterinary drugs market in SSA as well as on the international norms, recommendations, guidelines, and initiatives that impact SSA farmers' access to these drugs. Findings We highlight numerous barriers to veterinary drug access in SSA. The SSA market is highly dependent on imports, yet the region attracts little attention from the international companies capable of exporting to it. It suffers from a high level of fragmentation and weak distribution infrastructures and services, and is driven by the multiplication of private non-professional actors playing a growing role in the veterinary drug supply chain. The distribution system is increasingly dualized, with on the one hand the public sector (supported by development organizations) supplying small scale farmers in rural areas, but with limited and irregular means; and on the other side a private sector largely unregulated which supplies commercial and industrial farming systems. Different innovations have been developed at the international and regional levels to try to reduce barriers, such as homogenizing national legislations, donations, and vaccine banks. Alongside decades-old inter-state cooperation, many new forms of public-private partnerships and other hybrid forums continue to emerge, signaling the private sector's increasing influence in global governance. Conclusions Policies on animal health would be bolstered by a better understanding of the drivers behind and the components of access to veterinary drugs in different regional and national contexts. Inequalities in drug access need to be addressed and a market-driven approach adopted in order to strengthen our understanding of what determines veterinary drug use at the farm level. Policies should balance the interests of the various stakeholders, being careful not to reinforce bias toward certain diseases deemed “interesting” and neglect others that could prove to be highly important for veterinary public health.